A Rare Presentation Of Ewing's Sarcoma Involving Spine With Acute Paraplegia - Islam, Md Anowarul; Iqbal, Ahmed Asif; Parvez, Md Qumruzzaman; Goni, Md Fahad; Rana, Md Masud; Hossain, Mohd Alamgir (TAJ: Journal of Teachers Association, 2018)
Ewing's sarcoma is a primary bone malignancy with the highest incidence in the first decade of life. Although it mostly affects the diaphyseal as well as metaphysical region of growing long bones but involvement of spine is not very uncommon especially the sacrum. Nonsacral spinal Ewing's sarcoma is rarer and often mimics a benign condition before spreading extensively. They present with neurologic deficits due to spinal cord compression, but acute onset paraplegia is very rare.A high index of clinical suspicion can clinch the diagnosis early in the course of the disease. A prompt intervention is required to keep neurological damage to a minimum, and a correct combination of surgery, chemotherapy, and radiotherapy is required for better long-term patient outcome. We report a 15-years old male who presented with acute paraplegia and had an excellent postoperative outcome after posterior decompression of a D 11 Ewing's sarcoma. TAJ 2013; 26: 92-97